Management options of uterine leiomyoma patients admitted to a tertiary care hospital - Aktar, Toma; Mou, Farzana Naznin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Uterine fibroids (UFs), or uterine leiomyomas (UL), are the most common benign tumors of the female reproductive system, affecting a significant proportion of women of reproductive age. This study aims to evaluate the management strategies of UFs to optimize treatment approaches and patient outcomes. Methods: This cross-sectional study observational study was conducted department of obstetrics and gynecology, Shaheed Suhrawardy medical college hospital, Dhaka, from January 2022 to July 2022. A total of 100 women with fibroid were considered as study subjects by purposive sampling technique. Data analysis was done by statistical package of social sciences (SPSS) version 20.0. Results: The study highlights that UFs affect 20% to 80% of women by the age of 50, with an estimated global prevalence of 171 million cases. The incidence is 2 to 3 times higher among Black women than White women and first-degree relatives have a 2.2 times greater risk of developing fibroids. Imaging studies suggest that 3% to 7% of untreated fibroids in premenopausal women regress over 6 months to 3 years. Hysterectomy, the definitive treatment, accounts for 40% to 60% of all hysterectomies performed due to fibroids. Conclusions: In this study, it is observed that women with leiomyoma present with variable signs and symptoms. Menstrual disturbance, dysmenorrhea, pain in the lower abdomen, and anemia were the common clinical features. Almost half of the patients were managed by medical treatment whereas the rest of the portion was managed by either medical or surgical management and a few cases were managed by both medical and surgical treatment.